Nanomedicine: Challenges and Promises for Public Health Future - Ray, Subhashree; Tripathy , Debasmita (International Journal of Psychosocial Rehabilitation, 2019)
With the advancement of the scope applications of nanotechnology in medicine, it is important to identify and advance relevant contributions to public health at the same time. A broad range of nanomedicine advances promise to affect each medical specialty and reveal new ways to improve efficiency and prolong the lifetime-these improvements can be calculated at both population and individual levels. For instance, combined heart disease and cancer make up roughly half of all deaths, and developments in nanomedicine now show great potential to reduce morbidity and mortality rates related to these diseases. Meanwhile, the public health nanomedicine applications such as portable and rapid diagnostics and more efficient vaccinations have the ability to transform global health. Innovative science in fields such as biology, engineering, medicine, and public health will work together to achieve maximum possible health impacts for populations and individuals. In addition, gaps in information regarding the possible health and safety effects of exposure to the engineered nanomaterials need to be discussed and vigorously explored. Nanomedicine will be powered by innovative, constructive and socially responsible work as it plays an increasingly important and disruptive role in 21st century in medicine and public health.